Effectiveness of lockouts in reducing alcohol‐related harm: Systematic review. (19th April 2018) - Nepal, Smriti; Kypri, Kypros; Pursey, Kirrilly; Attia, John; Chikritzhs, Tanya; Miller, Peter
Abstract: Issues: Australian jurisdictions have introduced lockouts to prevent alcohol‐related violence. Lockouts prohibit patrons from entering licensed premises after a designated time while allowing sale and consumption of alcohol to continue. Their purposes include managing the movement of intoxicated patrons, and preventing violence and disorder by dispersing times that patrons leave premises. We sought to evaluate the effectiveness of lockouts in preventing alcohol‐related harm. Approach: We systematically searched electronic databases and reference lists and asked authors to identify relevant studies published to 1 June 2017. We deemed studies eligible if they evaluated lockouts, and if outcome measures included: assault, emergency department attendances, alcohol‐related disorders or drink‐driving offences. Two reviewers independently extracted data. Key Findings: After screening 244 records, we identified five studies from electronic databases, two from reference lists search and one from a Google search (N = 8). Two studies showed a decline in assaults; a third study showed reductions occurred only inside licensed premises; two studies showed an increase in assaults; and three studies showed no association. The studies had significant design and other limitations. Implications: Lockouts have been implemented across Australian jurisdictions as a strategy to prevent alcohol‐related harm, despite limited evidence. In this systematic review, we synthesised findings from studies that evaluated lockouts as stand‐alone interventions, to help clarify debate on their utility as a harm prevention strategy. Conclusion: There is not good evidence that lockouts prevent alcohol‐related harm, in contrast to what is known about stopping the sale of alcohol earlier, for which there is evidence of effectiveness.